N6-Methyladenosine Methylomic Landscape of Ureteral Deficiency in Reflux Uropathy and Obstructive Uropathy - Shi, Hua; Xiang, Tianchao; Feng, Jiayan; Yang, Xue; Li, Yaqi; Fang, Ye; Xu, Linan; Qi, Qi; Shen, Jian; Tang, Liangfeng; Shen, Qian; Wang, Xiang; et al. (Frontiers in Medicine, 2022)
Background Congenital anomalies of the kidneys and urinary tracts (CAKUT) represent the most prevalent cause for renal failure in children. The RNA epigenetic modification N6-methyladenosine (m6A) methylation modulates gene expression and function post-transcriptionally, which has recently been revealed to be critical in organ development. However, it is uncertain whether m6A methylation plays a role in the pathogenesis of CAKUT. Thus, we aimed to explore the pattern of m6A methylation in CAKUT. Methods Using m6A-mRNA epitranscriptomic microarray, we investigated the m6A methylomic landscape in the ureter tissue of children with obstructive megaureter (M group) and primary vesicoureteral reflux (V group). Results A total of 228 mRNAs engaged in multiple function-relevant signaling pathways were substantially differential methylated between the “V” and “M” groups. Additionally, 215 RNA-binding proteins that recognize differentially methylated regions were predicted based on public databases. The M group showed significantly higher mRNA levels of m6A readers/writers (YTHDF1, YTHDF2, YTHDC1, YTHDC2 and WTAP) and significantly lower mRNA levels of m6A eraser (FTO) according to real-time PCR. To further investigate the differentially methylated genes, m6A methylome and transcriptome data were integrated to identified 298 hypermethylated mRNAs with differential expressions (265 upregulation and 33 downregulation) and 489 hypomethylated mRNAs with differential expressions (431 upregulation and 58 downregulation) in the M/V comparison. Conclusion The current results highlight the pathogenesis of m6A methylation in obstructive and reflux uropathy.